Method for preparing wear-resistant super-hydrophobic anti-icing surface by nanosecond laser

By constructing a biomimetic armor-like composite rough structure using nanosecond lasers and controlling surface energy through low-temperature annealing, the problems of insufficient wear resistance and easy peeling of the coating on the superhydrophobic anti-icing surface were solved, achieving efficient preparation and improved stability of the wear-resistant superhydrophobic anti-icing surface.

CN123025009APending Publication Date: 2026-11-03JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611545519.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-10-08
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing superhydrophobic anti-icing surfaces suffer from insufficient wear resistance under high stress-low temperature coupling conditions, easy coating peeling, difficulty in achieving both hydrophobicity and anti-icing capabilities, and demanding chemical synthesis methods with poor structural controllability, making it difficult to achieve large-area uniform preparation.

Method used

A biomimetic armor composite rough structure is constructed using nanosecond lasers, and surface energy is controlled by low-temperature annealing. By building a micron armor structure and an internal micro-nano array on the surface of a metal substrate, a wear-resistant, superhydrophobic, and anti-icing surface is formed.

Benefits of technology

It achieves both wear resistance and superhydrophobicity without the use of external chemical coatings, has good cycle durability, can effectively prevent icing in low temperature and high humidity environments, and has a simple and controllable preparation method, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123025009A_ABST
    Figure CN123025009A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a wear-resistant super-hydrophobic anti-icing surface by using a nanosecond laser, relates to the technical field of laser processing and super-wetting metal materials, and takes the geometric shape of the triangular scales on the back of a hedgehog as a bionic prototype to design an armor structure. The nanosecond laser is used to perform internal and external triangular scanning processing on metal titanium, the laser process parameters are precisely controlled, the microscale armor structure and the internal micro-nano protrusion multistage bionic structure are constructed in situ on the metal surface by relying on the metal melting-recondensation mechanism, the microscale armor structure is higher than the micro-nano structure, can preferentially bear the contact stress in the wear process, effectively shields the direct damage of external force to the fragile micro-nano structure, and meanwhile, the internal micro-nano structure provides the roughness required by super-hydrophobicity. On this basis, the low-temperature annealing heat treatment process is combined to precisely control the surface energy and intrinsic wettability of the material, the surface super-hydrophobicity is realized, the contact area of liquid drops and the surface is reduced, and the icing time is significantly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser processing and superwetting metal materials technology, and more specifically, to a method for preparing wear-resistant, superhydrophobic, and anti-icing surfaces using nanosecond lasers. Background Technology

[0002] The aerospace, petrochemical, transportation, and marine engineering industries have an urgent need for metal-based superhydrophobic surfaces. Taking aerospace as an example, core components such as titanium alloy engine blades, gears, and bearings are at risk of icing, wear, and embrittlement under high-stress-low-temperature coupled conditions. Traditional superhydrophobic anti-icing surfaces are unsuitable for long-term service due to insufficient mechanical strength of their micro-nano structures. Therefore, developing durable metal-based superhydrophobic anti-icing surfaces that combine excellent superhydrophobicity with high wear resistance is of significant practical value for advancing engineering applications and extending the service life of metal components.

[0003] Currently, most developed wear-resistant superhydrophobic surfaces employ strategies such as coating reinforcement, composite structure design, and self-healing. However, they suffer from the following shortcomings: First, the wear-resistant function relies on external coatings, resulting in weak interfacial bonding between the coating and the substrate. Under cyclic friction, the coating is prone to peeling off, leading to the failure of the wear-resistant function. Second, existing composite structure designs often sacrifice some hydrophobicity to improve mechanical durability, thus weakening the surface's anti-icing and de-icing capabilities. Third, existing chemical synthesis methods are subject to stringent conditions and have poor structural controllability, making it difficult to achieve large-area uniform preparation and hindering industrial production.

[0004] Therefore, there is an urgent need for a method to prepare a wear-resistant superhydrophobic anti-icing surface that does not require an external chemical coating, has excellent superhydrophobicity and high wear resistance, can achieve efficient anti-icing in low temperature and high humidity environments, and has good cycle durability. Summary of the Invention

[0005] To address the aforementioned shortcomings in existing technologies, a method for preparing wear-resistant, superhydrophobic, and anti-icing surfaces using nanosecond lasers is provided. This method constructs a biomimetic armor-like composite rough structure using nanosecond lasers and combines it with low-temperature annealing to control surface energy, achieving both wear resistance and superhydrophobicity without the use of any external chemical coatings, thereby achieving low-temperature anti-icing performance.

[0006] The specific plan is as follows: The first aspect of this invention provides a method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond lasers, comprising the following steps: S1, Clean and pre-treat the surface of the metal substrate and then dry it; S2, On the surface of the metal substrate, a planar graphic of the armor structure is drawn using modeling software. The armor structure is composed of an array of multiple basic units. The basic unit is a concentric equilateral triangle structure, including an outer equilateral triangle outline and an inner equilateral triangle outline. The three sides of the outer equilateral triangle outline are parallel to the three sides of the inner equilateral triangle outline, respectively. S3, based on the armor structure of S2, takes the outline of each inner equilateral triangle as the reference and indents it by a certain distance. The equilateral triangle region obtained by indentation is the micro-nano array filling region. S4. A nanosecond laser is used to move along the contour path of the armor structure and perform inner and outer triangular scanning ablation on the surface of the metal substrate, causing the surface of the metal substrate to melt and resolidify, forming a micron armor structure in situ. S5 uses a nanosecond laser to perform a filling scan in the micro-nano array filling area to construct a micro-nano structure; S6 involves annealing the metal substrate after laser ablation to allow the surface of the metal substrate to adsorb organic carbon compounds in the environment, thereby regulating the surface energy and surface wettability, resulting in a biomimetic metal surface with superhydrophobic properties.

[0007] Preferably, in S2, the side length of the outer equilateral triangle profile is 800 μm, and the distance between the outer equilateral triangle profile and the inner equilateral triangle profile is 10 μm.

[0008] Preferably, in step S3, the distance by which the micro-nano array filling region is indented from the inner equilateral triangle outline is 10 μm.

[0009] Preferably, in S4, the inner and outer triangular scanning ablation includes two stages: outer equilateral triangle contour scanning and inner equilateral triangle contour scanning. First, the outer equilateral triangle contour is scanned: the laser beam completes the full area scan of path one along the direction parallel to the surface of the metal substrate, then completes the full area scan of path two along the direction of rotation 60° relative to path one, and then completes the full area scan of path three along the direction of rotation 60° relative to path two. The three scans together form the outer equilateral triangle contour. Then, the inner equilateral triangle contour is scanned: the laser beam scans along the inner equilateral triangle contour until all basic units have been scanned, and the scanned ablation trajectories together constitute the scanning path four.

[0010] Preferably, in S4, the micron-sized armor structure is as follows: the laser beam scans multiple times along the outer and inner equilateral triangle contours, so that the material at the inner and outer contours is fully melted and removed to form grooves. The area between the inner and outer contours is an unablated area, maintaining the original height, and forming a micron-sized protective ridge relative to the grooves on both sides. The width of the protective ridge is the distance between the outer and inner equilateral triangle contours.

[0011] Preferably, in S4, the process parameters of the nanosecond laser are: wavelength 1030-1090nm, pulse width 100-150ns, repetition frequency 15-30kHz, focused spot diameter 40-60μm, output power 3-10W, scanning speed 100-400mm / s, and number of scans 6-15.

[0012] Preferably, in step S5, the scanning of the micro-nano array filling area specifically involves: taking each micro-nano array filling area as a scanning unit, scanning each scanning unit independently, first scanning along a direction parallel to the metal substrate, then rotating the scanning direction by 90° and scanning along a direction perpendicular to the metal substrate, and finally scanning along the equilateral triangle boundary of the micro-nano array filling area to complete the independent unit scanning, and repeating the above process until all scanning units have been scanned.

[0013] Preferably, in step S5, the process parameters of the nanosecond laser are: wavelength 1030–1090 nm, pulse width 100–150 ns, repetition frequency 15–30 kHz, focused spot diameter 40–60 μm, output power 3–10 W, scan line spacing 10–100 μm, scanning speed 10–100 mm / s, and number of scans 1–5.

[0014] The second aspect of the present invention provides a wear-resistant, superhydrophobic, and anti-icing metal material, which is prepared using the method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser as described in the first aspect of the present invention.

[0015] Preferably, the metallic material is pure titanium.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes nanosecond laser scanning and ablation along a predetermined contour to construct an in-situ rough surface composed of micron-level biomimetic armor-like protective ridges and an internal lotus leaf-like micro / nano-level structure. No external coating is required; the armor structure is formed by the melting and resolidification of the metal substrate itself, exhibiting a continuous metallurgical bond with the substrate and eliminating the risk of delamination. During friction, the raised protective ridges preferentially bear the load, effectively dissipating wear energy and preventing abrasive particles from cutting and damaging the internal micro / nano-structure. This ensures the surface maintains structural integrity even after long-term wear, fundamentally avoiding hydrophobic performance failure due to damage to the micro / nano-structure, and exhibiting excellent service durability.

[0017] This invention relies on the pinning effect of the armor structure on the three-phase contact line of the droplet and the capillary force of the internal multi-level structure to generate a hydrophobic effect. Combined with the adsorption of organic compounds in the ambient air by low-temperature annealing, the surface energy is precisely controlled. Without the use of any low surface energy chemical modifiers, the surface is endowed with stable superhydrophobic properties, effectively preventing droplets from penetrating into the pits and maintaining a stable Cassie-Baxter composite interface, thereby achieving a synergistic improvement in wear resistance and superhydrophobic properties.

[0018] The preparation method of this invention only includes two main steps: nanosecond laser ablation and low-temperature annealing. It does not require complex processes such as hydrothermal synthesis, electrodeposition or chemical coating, nor does it require any chemical modifiers. The process is simple and controllable and environmentally friendly. Compared with traditional chemical methods, it has the advantages of high efficiency, good repeatability and easy control. Compared with picosecond and femtosecond laser processing, nanosecond lasers are low in cost and fast in processing speed, making them suitable for large-scale preparation of industrial emulsified oily wastewater treatment filters. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of a nanosecond laser scanning path along a preset contour in an embodiment of the present invention: Figure 1 In the diagram, a is the scanning path diagram of the armor structure fabrication, including the scanning of the outer equilateral triangle contour and the inner equilateral triangle contour, where the inset shows the scanning path of the inner equilateral triangle contour; b is a schematic diagram of the scanning contour of the internal micro-nano array filling region, where the inset shows the scanning path diagram of the internal equilateral triangle as an independent scanning unit; c is a schematic diagram of the composite rough structure of the titanium surface armor after laser scanning, where the side length, wall thickness of the armor protective ridge and the distance between the internal micro-nano array and the protective ridge are marked.

[0020] Figure 2 This is a scanning electron microscope (SEM) image of the titanium metal surface after laser ablation in an embodiment of the present invention; Figure 2 In the image, a is a low-magnification SEM image of the titanium sample in Comparative Experiment 2 of Example 2, showing the overall morphology of the titanium surface without laser ablation treatment; b is a high-magnification SEM image of the titanium sample in Comparative Experiment 2 of Example 2, showing the morphological details of the titanium surface without laser ablation treatment; c is a low-magnification SEM image of the titanium surface after laser ablation, showing the overall morphology of the surface armor composite rough structure; d is a morphological diagram of a single equilateral triangular armor composite rough structure, which includes an armor structure and an internal micro / nano structure; e is a schematic diagram of the height difference between the protective ridge and the internal micro / nano array; f is a detailed diagram of the independent multi-level structure in the internal micro / nano array, and the inset is a magnified view of the nanosphere particles.

[0021] Figure 3 The wettability test results of wear-resistant, superhydrophobic, and anti-icing titanium metal in the embodiments of the present invention are shown.

[0022] Figure 4 The test results of the friction and wear performance of wear-resistant, superhydrophobic, and anti-icing titanium metal in the embodiments of the present invention show the variation law of the friction coefficient with test time between the original surface and the armor structure sample in the friction and wear test.

[0023] Figure 5 The results show the anti-icing performance test results of wear-resistant, superhydrophobic, and anti-icing titanium metal in the embodiments of the present invention. Detailed Implementation

[0024] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings in the embodiments of the present invention.

[0025] Example 1: This embodiment provides a method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond lasers, including the following steps: S1, Metal substrate pretreatment: Cleaning and drying the surface of the metal substrate.

[0026] In this embodiment, titanium is used as the metal substrate. Commercially pure titanium is used, and the thickness of the titanium sample is approximately 2 mm, preferably 2 cm in both length and width. This titanium surface specification meets the requirements for friction and wear testing and is also convenient for laser processing.

[0027] The specific operation of step S1 is as follows: The original titanium sample is completely immersed in anhydrous ethanol and ultrasonically cleaned for 10-30 minutes at an ultrasonic frequency of 30-50 kHz to remove oil and organic contaminants from the surface of the titanium. After removal, it is completely immersed in deionized water and cleaned for 10-30 minutes under the same ultrasonic conditions to remove residual ethanol and soluble impurities. After cleaning, the titanium is allowed to air dry naturally at room temperature, or dried in a forced-air oven at 50-70℃ (preferably 60℃) for 10-30 minutes to obtain pretreated titanium. The ultrasonic cleaning time is preferably 20 minutes, and the ultrasonic frequency is preferably 40 kHz. The above cleaning steps effectively remove residual processing media, lubricant, and dust particles adhering to the surface of the titanium sample during processing, cutting, and storage, ensuring that laser energy can be uniformly applied to the clean metal surface during subsequent laser processing, avoiding uneven melting behavior caused by localized contaminants.

[0028] S2, Modeling an equilateral triangle armor structure: On the surface of a titanium metal sample, a planar design of an armor structure was drawn using modeling software. The armor structure is based on the geometric shape of the triangular scales on the back of a pangolin. The armor structure is composed of an array of multiple basic units. Each basic unit is a pair of concentric equilateral triangles, including an outer equilateral triangle outline and an inner equilateral triangle outline. The three sides of the outer equilateral triangle outline are parallel to the three sides of the inner equilateral triangle outline, and there is a predetermined distance between the sides of the two outlines. Adjacent basic units in the same horizontal row are 180° rotationally symmetrical, and one side of their outer equilateral triangle outlines overlaps.

[0029] The specific steps are as follows: Construction of a two-dimensional planar model of a titanium metal sample: In this embodiment, the titanium metal sample is preferably a square with a length and width of 2cm. Based on this size, the two-dimensional planar model is drawn as a square area of ​​2cm×2cm to ensure that the constructed armor structure pattern can completely cover the entire titanium surface in subsequent laser processing.

[0030] Construction of a two-dimensional planar model of an equilateral triangular armor structure: In this embodiment, the armor structure is composed of an array of multiple basic units. Each basic unit is drawn as a concentric equilateral triangle structure with a side length of 800 μm and a wall thickness of 10 μm. That is, the side length of the outer equilateral triangle contour of each basic unit is 800 μm, and the distance between the outer and inner equilateral triangle contours is 10 μm. After the basic units are arranged in an array, a complete array matching the size of the titanium metal sample can be formed.

[0031] The coordinated design of the geometric parameters of the armor structure in this invention is key to achieving a wear-resistant and superhydrophobic surface. Specifically: When the side length of a single basic unit is less than 800 μm and the wall thickness is less than 10 μm, the armor structure is too thin and cannot effectively withstand abrasive impacts. It does not provide sufficient physical barrier for the internal micro-nano structures, making the internal structures susceptible to wear and damage, and causing the superhydrophobic properties to deteriorate rapidly. When the side length of a single basic unit is greater than 800 μm and the wall thickness is greater than 10 μm, the structural unit size is too large, the number of basic units per unit area decreases, the proportion of micron-scale structures on the surface increases, the solid-liquid contact area increases, the stability of the Cassie-Baxter composite interface is destroyed, resulting in a significant loss of hydrophobic properties, which is not conducive to applications such as anti-icing.

[0032] S3, Establish the internal micro-nano array filling region: Based on the armor structure of S2, take the outline of each inner equilateral triangle as the reference and indent it inward by a certain distance. The resulting equilateral triangle region is the micro-nano array filling region.

[0033] In this embodiment, the distance inward from the inner equilateral triangle outline of the micro-nano array filling region is 10 μm, that is, the distance between the equilateral triangle outline of the micro-nano array filling region and the inner equilateral triangle outline of the basic unit is 10 μm.

[0034] The indentation distance of the micro / nano array filling region in this invention is one of the key parameters for achieving a wear-resistant superhydrophobic surface. Specifically: When the indentation distance is less than 10 μm, the boundary of the micro-nano array filling region is too close to the boundary of the basic unit. During laser processing, the heat-affected zone is prone to overlap, which leads to melting and deformation of the edge of the basic unit, blurring the geometric contour and weakening its physical barrier effect on the internal micro-nano structure. When the indentation distance is greater than 10 μm, the interval between the micro-nano array filling region and the basic unit increases, and a wider transition region appears between the micro-nano array and the basic unit. This region lacks micro-nano structure coverage and is prone to becoming a preferred pinning site for droplets during wetting, which disrupts the continuity of the Cassie-Baxter composite interface and leads to the loss of superhydrophobic properties.

[0035] S4, Nanosecond Laser Contouring: A nanosecond laser is used to move along the contour path of the armor structure, performing inner and outer triangular scanning ablation on the surface of the metal substrate. This causes the surface of the metal substrate to melt and resolidify, forming a micron-sized armor structure in situ. Specifically, this includes the following aspects: Laser processing equipment and parameters: In this embodiment, the nanosecond pulsed laser is a nanosecond pulsed fiber laser with an output wavelength of 1030–1090 nm, preferably 1060 nm. Lasers of this wavelength have a high absorption rate on the surface of titanium metal, effectively achieving rapid melting of the metal. The pulse width is 100–150 ns, preferably 120 ns; the repetition frequency is 15–30 kHz, preferably 20 kHz; the focused spot diameter is 40–60 μm, preferably 50 μm; the output power is 3–10 W, preferably 5 W; the scanning speed is 100–400 mm / s, preferably 200 mm / s; and the number of scans is 6–15, preferably 10.

[0036] In this embodiment, the optimal parameter range for ensuring that the molten metal forms a sufficiently high armor structure under the action of surface tension and avoiding over-fusion or insufficient ablation is achieved by the coordinated combination of output power of 3 to 10W, scanning speed of 100 to 400 mm / s, and scanning times of 6 to 15. Exceeding this range will prevent the formation of a clear and suitable armor structure.

[0037] The output power directly determines the energy density of the laser acting on the surface of titanium. When the power is below 3W, the laser energy is insufficient to fully melt the titanium surface, resulting only in shallow ablation marks and failing to form a distinctive armor structure. When the power is above 10W, the excessive laser energy causes over-melting of the titanium surface, increasing the fluidity of the molten pool. The splashed molten material adheres to each other and forms a continuous and disordered cladding layer, making it difficult to obtain an armor structure with clear boundaries and uniform thickness.

[0038] The scanning speed determines the duration of the interaction between the laser and the material. When the scanning speed is in the range of 100–400 mm / s, a sufficient molten pool can be formed at each laser pulse location, promoting the complete melting of the base metal and thus forming a highly uniform armor structure. If the scanning speed is too high, the material melting duration is insufficient, making it difficult to prepare a sufficiently high and uniform armor structure; if the scanning speed is too low, the molten pool duration will be prolonged, causing excessive melting and coalescence of the molten material, ultimately resulting in a blurred outline of the armor structure.

[0039] The number of scans determines the cumulative energy input of the laser to the same area. When the number of scans is 6 to 15, the cumulative energy effect of the laser on the titanium substrate is moderate. This avoids insufficient melting depth and low armor structure height due to too few scans, while also preventing excessive heat accumulation and excessive melt spread due to too many scans. A maximum of 10 scans, combined with the aforementioned power and scanning speed parameters, ensures a stable and controllable remelting effect on the substrate surface, which is beneficial for constructing an armor structure with regular morphology, uniform height, and excellent wear resistance.

[0040] The inner and outer triangular scanning strategies are as follows: The inner and outer triangular scanning ablation includes two stages: outer equilateral triangle contour scanning and inner equilateral triangle contour scanning. The specific operation is as follows: The pretreated titanium sample is placed flat and fixed on the laser processing stage to ensure that the titanium surface is flat and without positional displacement. The outer equilateral triangle contour scanning begins: the laser beam completes the full area scanning of path one in a direction parallel to the surface of the metal substrate, then completes the full area scanning of path two in a direction rotated 60° relative to path one, and then completes the full area scanning of path three in a direction rotated 60° relative to path two. The three scans together form the outer equilateral triangle contour. Then, the inner equilateral triangle contour is scanned: the laser beam scans along the inner equilateral triangle contour until all basic units have been scanned, and the scanned ablation trajectories together constitute the scanning path four.

[0041] The advantage of the aforementioned inner and outer triangular scanning strategy lies in the fact that the wear-resistant, superhydrophobic, and anti-icing surface is composed of a densely packed array of basic armor-like units, filling the entire surface. There are overlapping areas between adjacent basic units. If an independent scanning scheme is used, the overlapping areas will concentrate on the outer side of the basic units, resulting in a doubling of the number of scans and causing uneven height of the armor structure between the inner and outer regions. Therefore, this triangular scanning method is a key operation in fabricating a highly uniform armor structure.

[0042] The formation mechanism of armor structure: The aforementioned in-situ formation of an armored composite rough structure using nanosecond lasers involves the following process: When a nanosecond pulsed laser is focused onto the surface of a titanium substrate, the metal absorbs the laser energy and converts it into heat, causing a localized area on the titanium surface to heat up above its melting point in a very short time, forming a micron-sized molten pool and achieving rapid material removal. The laser beam scans the inner and outer equilateral triangle contours 10 times each. The repeated melting and removal of material at the inner and outer contours creates grooves; the area between the inner and outer contours remains un-ablated, essentially maintaining its original height, and forms a micron-sized protective ridge relative to the grooves on either side. The protective ridge has a set side length of 800 μm and a set wall thickness of 10 μm, providing protection.

[0043] S5, Nanosecond Laser Construction of Micro / Nano Arrays: A nanosecond laser is used to perform a fill-in scan on the filled area of ​​the micro / nano array to construct micro / nano structures. This specifically includes the following aspects: Laser processing equipment and parameters: In this embodiment, the nanosecond pulsed laser is a nanosecond pulsed fiber laser with an output wavelength of 1030–1090 nm, preferably 1060 nm. This wavelength of laser light has a high absorption rate on the surface of titanium metal, effectively achieving rapid melting of the metal. The pulse width is 100–150 ns, preferably 120 ns; the repetition frequency is 15–30 kHz, preferably 20 kHz; the focused spot diameter is 40–60 μm, preferably 50 μm; the output power is 3–10 W, preferably 5 W; the scanning speed is 10–100 mm / s, preferably 50 mm / s; the scanning spacing is 10–100 μm, preferably 50 μm; and the number of scans is 1–5, preferably 1.

[0044] In this embodiment, the optimal parameter range for ensuring rapid solidification of molten metal into micro / nano structures under surface tension, while avoiding over-fusion or insufficient ablation, is achieved by using an output power of 3–10 W, a scanning speed of 10–100 mm / s, a scanning spacing of 10–100 μm, and a scanning frequency of 1–5 times. Exceeding this range will prevent the formation of complete periodic micro / nano structures. Specifically: When the power is below 3W, the laser energy is insufficient to fully melt the surface material of the titanium metal, and can only produce shallow ablation marks, unable to form obvious micron-sized protrusions. When the power is above 10W, the laser energy is too high, causing the surface material of the titanium metal to over-melt or even vaporize. The molten material is too fluid, and the splashed material merges with each other to form a continuous irregular cladding layer, unable to form independent micro-nano structures.

[0045] When the scanning speed is below 10 mm / s, the number of laser pulses received in the same area is too large, resulting in a significant energy accumulation effect that can easily cause surface breakdown and structural damage. When the scanning speed is above 100 mm / s, the number of pulses acting on the titanium substrate is insufficient, and only discontinuous micron-sized protrusions can be generated on the surface.

[0046] The line spacing determines the degree of overlap between adjacent scan trajectories. When the line spacing is 10–100 μm, the molten areas of adjacent scan trajectories can overlap appropriately, avoiding both discontinuity in the processing area due to excessive spacing and excessive heat accumulation due to insufficient spacing.

[0047] Fill-in scanning strategy within the micro / nano array filling region: Each micro-nano array filling region is used as a scanning unit. Each scanning unit is scanned independently. First, the scanning direction is parallel to the metal substrate. Then, the scanning direction is rotated by 90° and scanned perpendicular to the metal substrate. Finally, the scanning direction is scanned along the equilateral triangle boundary of the micro-nano array filling region to complete the scanning of the independent unit. The above process is repeated until all scanning units are scanned.

[0048] The formation mechanism of internal micro / nano structures: During the fill-in scanning of the internal region, nanosecond pulsed lasers rapidly heat the titanium surface to above its melting point, forming micro-molten pools. The molten titanium flows under surface tension, and after the laser is removed, it rapidly cools and re-solidifies, forming micron-sized parabolic protrusions. Simultaneously, the titanium vapor and plasma generated by laser ablation cool and condense, forming nano-sized spherical molten protrusions. These micron-sized and nano-sized protrusions superimpose to form a multi-level roughened structure resembling a lotus leaf on the titanium surface in situ. This structure is firmly bonded to the titanium matrix, located inside the protective ridge, and together with the ridge, constitutes a wear-resistant, superhydrophobic, and anti-icing surface.

[0049] S6, Low-temperature annealing treatment: Annealing treatment is performed on the metal substrate after laser ablation, so that the surface of the metal substrate adsorbs organic carbon compounds in the environment to regulate the surface energy and surface wettability, resulting in a biomimetic metal surface with superhydrophobic properties.

[0050] In this embodiment, the annealing temperature is 110–150°C, and the time is 1–3 hours. Preferably, the annealing temperature is 130°C, and the annealing time is 2 hours. The annealing process is carried out in a forced-air oven to ensure uniform temperature and air circulation within the oven.

[0051] The surface of titanium metal ablated by nanosecond laser exhibits high roughness, a significantly increased specific surface area, and high surface free energy, resulting in superhydrophilicity in air (water contact angle close to 0°). The laser-ablated samples are then subjected to low-temperature annealing in a forced-air oven. On one hand, under heating conditions, organic compounds in the ambient air (such as volatile organic compounds and trace amounts of oil vapor) are adsorbed onto the high specific surface area of ​​the titanium metal, forming a monolayer or sub-monolayer adsorption. These adsorbed species effectively reduce the surface free energy of the titanium metal surface, bringing it to a suitable moderate surface energy level. On the other hand, the annealing process also helps eliminate residual stress generated during laser processing and stabilizes the surface oxide layer.

[0052] The choice of annealing temperature is crucial: if the temperature is too low (e.g., below 110℃), the adsorption rate of organic compounds is too slow, and the adsorbed layer is not stable enough, making it difficult to effectively regulate surface energy within a reasonable time. If the temperature is too high (e.g., above 150℃), the adsorbed organic compounds may desorb or decompose, leading to failure of surface energy regulation. Furthermore, excessively high temperatures may cause excessive oxidation of the titanium surface, affecting the final wettability. An annealing time of 1–3 hours ensures that the adsorption process reaches equilibrium, stabilizing surface wettability. Figure 3 As shown, the surface of the armor composite structure exhibits excellent superhydrophobicity after annealing for 2 hours.

[0053] After annealing, the sample was removed from the oven and allowed to cool naturally to room temperature in the air. During the natural cooling process, as the temperature decreased, the adsorbed organic compound layer gradually solidified, and the surface energy state was "frozen," thus obtaining stable and repeatable wetting properties.

[0054] In summary, this invention achieves wear-resistant and superhydrophobic properties through a purely physical method of "laser-constructed physical structure + annealing to fine-tune surface energy" without using any external chemical coatings (such as low surface energy modifiers like fluorosilanes or long-chain thiols). This technical approach avoids the problem of chemical coatings peeling off and failing during repeated use, fundamentally improving the durability and stability of the material.

[0055] The wettability of the wear-resistant, superhydrophobic, and anti-icing surface prepared by the above method is as follows: The wear-resistant superhydrophobic surface prepared by the above method consists of a biomimetic micron-scale armor structure and an internal micro / nano array, forming a biomimetic multi-level structure. The armor structure is arranged in concentric equilateral triangles with a periodic arrangement, a side length of 800 μm, a wall thickness of 10 μm, and a protrusion height of 10 μm. The internal filling region is a micro / nano multi-level structure constructed by nanosecond laser secondary scanning, with an adjacent protrusion spacing of 50 μm. Nanospherical particles are attached to the surface of the micron-scale parabolic protrusions. These nanospherical particles originate from the solidification products of microdroplets splashed at the edge of the molten pool and from fine spherical particles generated by secondary melting and resolidification on the protrusion surface. Together, they constitute the fine layers of a lotus leaf-like multi-level rough structure. In addition to acting as a physical barrier to improve wear resistance, the geometric contour of the periodic protrusions also creates a pinning effect on the three-phase contact line of the droplets, inhibiting droplet spreading on the surface. This, combined with the capillary forces of the internal micro / nano structure, maintains a stable Cassie-Baxter composite interface, thereby significantly improving the surface's superhydrophobic properties. Figure 3 As shown, after annealing, the surface exhibits excellent superhydrophobic properties, with a contact angle of 151.4° and a roll-off angle of 10.3°.

[0056] The frictional properties of the wear-resistant, superhydrophobic, and anti-icing surface prepared by the above method are as follows: The wear-resistant, superhydrophobic, and anti-icing surface prepared using the above method has an outer armor structure arranged in a periodic pattern of equilateral triangles, with a side length of 800 μm and a wall thickness of 10 μm, which is 10 μm higher than the protrusion height of the inner micro-nano array. In a dry friction and wear test, the prepared wear-resistant, superhydrophobic, and anti-icing surface was used for friction. The grinding balls were 6.5 mm diameter silicon nitride ceramic balls, with a reciprocating stroke of 5 mm, a reciprocating frequency of 10 Hz, and a friction time of 10 min. During the experiment, the periodically arranged equilateral triangle armor ridges preferentially contact the grinding balls, serving as the main load-bearing units and physical barriers, preventing the internal micro-nano structures from directly bearing frictional shear. The grooves between the protective ridges can accommodate wear debris, reducing abrasive wear. Figure 4 As shown, the steady-state friction coefficient of the wear-resistant superhydrophobic anti-icing surface remains in the range of 0.75 to 0.88, and the fluctuation of the friction coefficient is significantly reduced, demonstrating good friction reduction effect and friction stability. This confirms that the armor structure can effectively optimize the contact and wear behavior of the friction interface.

[0057] The macroscopic dimensions of titanium can be adjusted according to actual application requirements. The typical sample size set in this embodiment is 2cm×2cm, but it can also be scaled up to any size required for engineering applications to meet the anti-icing needs of surfaces of different scales.

[0058] Example 2: This embodiment uses specific performance verification experiments to test and verify the anti-icing performance of the wear-resistant, superhydrophobic, and anti-icing titanium metal prepared according to the above-mentioned preferred implementation parameters. The following experiments all use samples prepared according to the above-mentioned preferred implementation parameters, and are used to exemplify the feasibility and beneficial effects of the present invention, and do not constitute a limitation on the scope of protection of the present invention.

[0059] Verification experiment on the anti-icing performance of wear-resistant, superhydrophobic, and anti-icing titanium metal: This performance verification experiment is a specific example of preparing wear-resistant, superhydrophobic, and anti-icing titanium metal according to the preferred processing parameters of the above preparation method and testing its anti-icing performance.

[0060] A 2cm×2cm square titanium sample was selected and completely immersed in anhydrous ethanol and deionized water in sequence. The sample was ultrasonically cleaned for 20 minutes each at an ultrasonic frequency of 40kHz. After cleaning, the sample was placed in a 60℃ forced-air oven and dried for 15 minutes to obtain pretreated titanium.

[0061] A 2cm×2cm rectangular area was constructed using modeling software. Then, concentric equilateral triangles with a side length of 800μm and a wall thickness of 10μm were used as basic units and distributed in an array on the surface of the substrate to draw the planar graphic of the armor structure.

[0062] Based on the armor structure constructed above, taking the inner boundary of each concentric equilateral triangle as the reference, it is indented by 10μm. The resulting equilateral triangle region is the micro-nano array filling region. The boundary of the micro-nano array filling region is parallel and concentric with the outline of the armor structure.

[0063] Nanosecond pulsed fiber lasers were used to perform internal and external triangular scanning ablation on pretreated titanium. The laser parameters were set as follows: wavelength 1060 nm, pulse width 120 ns, repetition rate 20 kHz, focused spot diameter 50 μm, output power 5 W, scanning speed 200 mm / s, and 10 scans. The scanning path is as follows. Figure 1 As shown in Figure a, the pretreated titanium sample is placed flat and fixed on the laser processing stage for internal and external triangular scanning ablation. First, the outer equilateral triangle contour is scanned: the laser beam completes the full area scan of path one along a direction parallel to the surface of the metal substrate, then completes the full area scan of path two along a direction rotated 60° relative to path one, and then completes the full area scan of path three along a direction rotated another 60° relative to path two. The three scans together form the outer equilateral triangle contour. Then, the inner equilateral triangle contour is scanned: the laser beam scans along the inner equilateral triangle contour until all basic units have been scanned. The scanning ablation trajectories together form scanning path four.

[0064] Based on the constructed armor structure, nanosecond laser technology was used to perform a fill-in scan along the internal region to construct the micro / nano structure. The laser parameters were set as follows: wavelength 1060 nm, pulse width 120 ns, repetition rate 20 kHz, focused spot diameter 50 μm, output power 5 W, scan line spacing 50 μm, scanning speed 50 mm / s, and one scan. The scanning path is as follows. Figure 1 As shown in b. Using the equilateral triangles formed by indenting the inner equilateral triangle outline of the basic unit by 10 μm as scanning units, each scanning unit is scanned independently: first, scan along a direction parallel to the titanium surface; then, rotate the scanning direction by 90° and scan along a direction perpendicular to the titanium surface; finally, scan along the boundary of the equilateral triangle to complete the independent unit scan. This process is repeated until all scanning units are scanned, completing the internal region filling scan.

[0065] The laser-ablated titanium metal was placed in a forced-air drying oven and annealed at a constant temperature of 130℃ for 2 hours. After annealing, it was naturally cooled to room temperature in the air to obtain wear-resistant, superhydrophobic, and anti-icing titanium metal with superhydrophobic properties.

[0066] The wear-resistant, superhydrophobic, and anti-icing titanium metal prepared in this performance verification experiment was characterized by scanning electron microscopy. After laser ablation, a composite rough structure composed of a micron-scale armor structure and an internally filled micro / nano array was formed on the surface of the titanium metal. Figure 2 As shown in image c, the low-magnification SEM image reveals that the armor structure has an equilateral triangular outline with clear and continuous boundaries, and is evenly distributed throughout the processing area in a periodic manner. Figure 2 As shown in Figure d, the single equilateral triangular armor composite rough structure includes an outer protective ridge and an inner micro / nano array. The protective ridge forms a closed equilateral triangular frame, and the inner micro / nano array fills its inner side. The armor structure has a side length of approximately 800 μm, and the protective ridge wall thickness is approximately 10 μm. Figure 2 As shown in figure e, there is a significant height difference between the protective ridge and the internal micro / nano array. The protective ridge protrudes above the internal micro / nano array, thus forming a protective space inside the protective ridge. The protrusion height is approximately 10 μm. Figure 2 As shown in f, the internal micro-nano array consists of micrometer-scale parabolic protrusions and nanometer-scale spherical particles attached to their surface, with the spacing between adjacent micrometer-scale protrusions being approximately 50 μm. Figure 2 The inset in f is a magnified view of a part of the nanostructure, showing that spherical particles of about 20 nm are uniformly attached to the micron-sized protruding surface, and the two together constitute a lotus leaf-like multi-level rough structure.

[0067] The wear-resistant, superhydrophobic, and anti-icing titanium alloy prepared for this performance verification experiment was subjected to wettability testing, such as... Figure 3As shown, when the annealing time reaches 2 hours, the surface exhibits excellent superhydrophobic properties, with a contact angle of 151.4° and a roll-off angle of 10.3°. This superhydrophobic property is achieved through the synergy of a micron-scale armor structure and an internal micro / nano-scale multi-level structure: the internal micro / nano-scale multi-level structure consists of micron-scale parabolic protrusions and nano-scale spherical particles, which can trap air to form a Cassie-Baxter interface, reducing solid-liquid contact and inhibiting droplet wetting; the armor protective ridges protruding on the micro / nano array act as a physical barrier to pin the three-phase contact lines, limiting droplet spread and preventing the micro / nano structure from directly bearing frictional shear.

[0068] The wear-resistant, superhydrophobic, and anti-icing titanium alloy prepared in this performance verification experiment was subjected to tribological tests, such as... Figure 4 As shown in the figure, during the initial running-in stage, the friction coefficient of the sample surface increased gradually with small fluctuations and no abrupt peaks, indicating that the armor structure can weaken the initial adhesion effect and improve the running-in stability. After entering the steady-state wear stage, the friction coefficient stabilized at 0.75~0.88, with the average friction coefficient decreasing by about 36% compared to the original surface, and the fluctuation was significantly reduced, demonstrating good friction reduction effect and friction stability. The above results indicate that the armor structure can optimize the contact and wear behavior of the friction interface and promote the establishment of a stable wear state.

[0069] The anti-icing performance of the wear-resistant, superhydrophobic, and anti-icing titanium metal prepared in this performance verification experiment was tested, such as... Figure 5 As shown.

[0070] The cooling stage temperature was set to -15℃. After the temperature stabilized, the sample was placed flat on the cooling stage, and a 10μL test droplet was placed on its surface. The cooling dynamics of the droplet were observed in real time using a side-view profilometer. Initially, the droplet outline was clear and it appeared as a transparent sphere. After 605s, the droplet instantly became opaque, entering a supercooled state of solid-liquid coexistence. Subsequently, the solid-liquid interface moved upward from the bottom of the droplet, and rapid crystallization occurred after 612s. The droplet was completely frozen after 650s, marking the completion of freezing.

[0071] This performance verification experiment confirms that the wear-resistant, superhydrophobic, and anti-icing titanium metal prepared by this invention is composed of a micron-scale armor structure and an internal micro / nano array. The synergy of these two components gives the surface excellent superhydrophobicity, wear resistance, and anti-icing properties. Under -15℃ cold stage conditions, the freezing time of droplets on the surface of this invention is extended to 650 s.

[0072] Comparative verification experiment on the necessity of armor: Comparative Experiment 1: Except for the change of the nanosecond laser ablation parameter in step S4 to 5 scans, the other process conditions in this comparative performance verification experiment were consistent with those in the preparation and anti-icing performance verification experiment of the wear-resistant superhydrophobic anti-icing surface.

[0073] The same testing apparatus as used in the wear resistance and anti-icing performance verification experiments described above was employed. The results showed that because the number of inner and outer contour scans for this comparative sample was less than six, no obvious protective ridges formed on the surface, and the geometric contour tended to be flat. This made it difficult to effectively withstand and dissipate the impact load generated by abrasive particles during friction, resulting in the internal micro / nano structure being directly exposed to the wear environment. Therefore, the wear resistance, superhydrophobic stability, and anti-icing performance of this comparative sample were all significantly reduced.

[0074] The results of the comparative performance verification experiment show that when the number of scans is less than 6, the height of the constructed armor structure is insufficient, making it difficult to effectively protect the internal micro-nano array. As a result, the internal structure is directly exposed to abrasive impact during friction, the surface wear resistance is significantly reduced, and thus the superhydrophobic properties deteriorate rapidly.

[0075] Comparative Experiment 2: Except for steps S2-S5, the process conditions in this comparative performance verification experiment were consistent with those in Example 1 for the preparation and anti-icing performance verification of wear-resistant superhydrophobic anti-icing titanium.

[0076] Select 2×2cm titanium metal of the same specifications as in the above verification experiment, and use the same cleaning and pretreatment steps. Then, place the cleaned titanium metal directly into a forced-air drying oven and anneal at a constant temperature of 130℃ for 2 hours. After annealing, allow it to cool naturally to room temperature in the air to obtain the comparison sample.

[0077] like Figure 2 As shown in a and 2b, the field emission scanning electron microscopy characterization results show that the surface of the comparison sample has a smooth and flat morphology, without any micron-scale armor structure, and no micro-nano arrays filled inside were observed.

[0078] The testing apparatus was identical to that used in the aforementioned wear-resistant, superhydrophobic, and anti-icing surface wear and anti-icing performance verification experiments. The results showed that: Comparative Experiment 2 results show that, even after the same annealing treatment, the wear resistance of surfaces without nanosecond laser-constructed armor structures remains unchanged. For example... Figure 4 As shown, during the initial running-in stage, the original surface friction coefficient rapidly increases and fluctuates dramatically, exhibiting multiple significant peaks, with the peak friction coefficient exceeding 1.5. This indicates strong interfacial adhesion and extreme instability of the friction interface during the initial contact stage. After entering the steady-state wear stage, the friction coefficient continuously fluctuates within the range of 1.2 to 1.35, with an average friction coefficient of approximately 1.28. This demonstrates that the friction interface remains in a dynamically unstable state of adhesion-delamination, making it difficult to form a stable wear interface. This proves that the laser-constructed micron-sized armor structure is a necessary condition for achieving the wear-resistant and superhydrophobic synergistic effects of this invention.

[0079] In summary, the method for preparing wear-resistant, superhydrophobic, and anti-icing surfaces using nanosecond lasers provided by this invention comprises only two core steps: laser ablation and low-temperature annealing. It eliminates the need for complex processes such as hydrothermal synthesis, electrodeposition, or chemical coating, resulting in a concise and highly controllable process. Compared to picosecond and femtosecond lasers, the nanosecond laser used offers significant advantages in terms of lower equipment cost, higher processing efficiency, and ease of industrial integration. The prepared biomimetic armor-like surface significantly enhances the wear resistance and anti-icing properties of the substrate, and the entire process requires no external assistance, making it suitable for large-scale industrial processing.

[0080] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or step transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser, characterized in that, Includes the following steps: S1, Clean and pre-treat the surface of the metal substrate and then dry it; S2, On the surface of the metal substrate, a planar graphic of the armor structure is drawn using modeling software. The armor structure is composed of an array of multiple basic units. The basic unit is a concentric equilateral triangle structure, including an outer equilateral triangle outline and an inner equilateral triangle outline. The three sides of the outer equilateral triangle outline are parallel to the three sides of the inner equilateral triangle outline, respectively. S3, based on the armor structure of S2, takes the outline of each inner equilateral triangle as the reference and indents it by a certain distance. The equilateral triangle region obtained by indentation is the micro-nano array filling region. S4. A nanosecond laser is used to move along the contour path of the armor structure and perform inner and outer triangular scanning ablation on the surface of the metal substrate, causing the surface of the metal substrate to melt and resolidify, forming a micron armor structure in situ. S5 uses a nanosecond laser to perform a filling scan in the micro-nano array filling area to construct a micro-nano structure; S6 involves annealing the metal substrate after laser ablation to allow the surface of the metal substrate to adsorb organic carbon compounds in the environment, thereby regulating the surface energy and surface wettability, resulting in a biomimetic metal surface with superhydrophobic properties.

2. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S2, the side length of the outer equilateral triangle profile is 800 μm, and the distance between the outer equilateral triangle profile and the inner equilateral triangle profile is 10 μm.

3. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S3, the distance by which the micro-nano array filling region is indented from the inner equilateral triangle outline is 10 μm.

4. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S4, the inner and outer triangular scanning ablation includes two stages: outer equilateral triangle contour scanning and inner equilateral triangle contour scanning. First, the outer equilateral triangle contour is scanned: the laser beam completes the full area scan of path one along the direction parallel to the surface of the metal substrate, then completes the full area scan of path two along the direction of rotation 60° relative to path one, and then completes the full area scan of path three along the direction of rotation 60° relative to path two. The three scans together form the outer equilateral triangle contour. Then, the inner equilateral triangle contour is scanned: the laser beam scans along the inner equilateral triangle contour until all basic units have been scanned, and the scanned ablation trajectories together constitute the scanning path four.

5. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S4, the micron armor structure is as follows: the laser beam scans the outer equilateral triangle contour and the inner equilateral triangle contour multiple times, so that the material at the inner and outer contours is fully melted and removed to form grooves. The area between the inner and outer contours is an unablated area, maintaining the original height, and forming a micron-level protective ridge relative to the grooves on both sides. The width of the protective ridge is the distance between the outer equilateral triangle contour and the inner equilateral triangle contour.

6. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S4, the process parameters of the nanosecond laser are: wavelength 1030-1090nm, pulse width 100-150ns, repetition frequency 15-30kHz, focused spot diameter 40-60μm, output power 3-10W, scanning speed 100-400mm / s, and number of scans 6-15.

7. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S5, the scanning of the micro-nano array filling area is specifically as follows: taking each micro-nano array filling area as a scanning unit, each scanning unit is scanned independently. First, the scanning direction is rotated 90° and then the scanning direction is rotated to scan along the direction perpendicular to the metal substrate. Finally, the scanning is performed along the equilateral triangle boundary of the micro-nano array filling area to complete the independent unit scanning. The above process is repeated until all scanning units are scanned.

8. The method for preparing a wear-resistant, superhydrophobic, and anti-icing surface using nanosecond laser according to claim 1, characterized in that, In S5, the process parameters of the nanosecond laser are: wavelength 1030-1090nm, pulse width 100-150ns, repetition frequency 15-30kHz, focused spot diameter 40-60μm, output power 3-10W, scan line spacing 10-100μm, scanning speed 10-100mm / s, and number of scans 1-5.

9. A wear-resistant, superhydrophobic, anti-icing metallic material, characterized in that, The surface was prepared using the method described in any one of claims 1 to 8, which utilizes nanosecond lasers to prepare a wear-resistant, superhydrophobic, and anti-icing surface.

10. The wear-resistant, superhydrophobic, and anti-icing metal material according to claim 9, characterized in that, The metallic material is pure titanium.